(untitled) (Northern International Medical College Journal, 2021)
Apert syndrome is a rare type I acrocephalosyndactyly syndrome having autosomal dominant inheritance due to mutations in the fibroblast growth factor receptors gene. New or fresh mutations are also frequent. It is characterized by dysmorphic face, craniosynostosis, severe syndactyly of the hands and feet. Apert syndrome affects the first branchial or pharyngeal arch, the precursor of the maxilla and mandible. Disturbances in the development of branchial arches during fetal period create extensive malformation in different parts of the body. Management of Apert syndrome requires a multidisciplinary approach. We, hereby, report a case of a 45-days old baby with Apert syndrome. Northern International Medical College Journal Vol.11 (2) Jan 2020: 475-477